2010
DOI: 10.1002/jnr.22515
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for large‐scale generation of dopamine neurons from human embryonic stem cells

Abstract: Dopamine (DA) neurons derived from human embryonic stem cells (hESCs) are potentially valuable in drug screening and as a possible source of donor tissue for transplantation in Parkinson's disease. However, existing culture protocols that promote the differentiation of DA neurons from hESCs are complex, involving multiple steps and having unreliable results between cultures. Here we report a simple and highly reproducible culture protocol that induces expandable DA neuron progenitors from hESCs in attached cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 44 publications
(67 reference statements)
0
16
0
Order By: Relevance
“…Presence of TH and NURR1 positive cells in our culture confirms that some of the cells are dopaminergic in nature. It has been shown that human ES-derived neuronal progenitors could be differentiated into neurons, exhibiting midbrain DA phenotype, expressing Aldh1a, PTX3, NURR1 and LMX1a by repeated passaging in the presence of basic fibroblast growth factor and medium conditioned with PA6 stromal cells [28]. Studies have shown that DA neurons acquiring SNpc specificity requires PITX3 to be induced [29].…”
Section: Discussionmentioning
confidence: 99%
“…Presence of TH and NURR1 positive cells in our culture confirms that some of the cells are dopaminergic in nature. It has been shown that human ES-derived neuronal progenitors could be differentiated into neurons, exhibiting midbrain DA phenotype, expressing Aldh1a, PTX3, NURR1 and LMX1a by repeated passaging in the presence of basic fibroblast growth factor and medium conditioned with PA6 stromal cells [28]. Studies have shown that DA neurons acquiring SNpc specificity requires PITX3 to be induced [29].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, ES cells offer sources for large-scale production of neurons which acquire a midbrain DA phenotype. 40, 41 Grafting both ES- and MSC-derived DA neurons into rat PD models results in functional recovery. 42, 43 The ability to produce patient-specific DA neurons has recently been demonstrated using iPS cells.…”
Section: Cellular Therapy For Neurodegenerative Diseasesmentioning
confidence: 99%
“…This factor has been reported to help in maintaining the specific properties of different progenitor cell types. For example, hESC-derived neuronal progenitors were found to retain their full capacity to generate dopamine neurons after repeated passaging in the presence of FGF2 (Morizane et al, 2010). FGF2 has been shown to increase the lifespan and potential for differentiation of mesenchymal stem cells from the bone marrow (Bianchi et al, 2003).…”
Section: Discussionmentioning
confidence: 99%